Pterygoid Hamulus Bursitis: A Rare Intra-Oral Pain Syndrome. Issue 7 (October 2019) - Thukral, Himanshu; Nagori, Shakil Ahmed; Rawat, Aditi; Jose, Anson
Abstract : Abstract: Pterygoid hamular bursitis is a rare craniofacial pain syndrome used to describe palatal and pharyngeal pain due to an enlarged pterygoid hamulus. The pterygoid hamulus is a hook-shaped bony process located bilaterally on each medial pterygoid plate of the sphenoid bone, posterior and medial to each maxillary tuberosity. These processes project downward and anterolaterally; serve as attachment for ligaments and a network of muscles. It can be palpated in patients with a finger palpating the posteromedial to maxillary tuberosity. The pathogenesis is elusive and varies from bursitis of tensor veli palatine, elongated pterygoid hamulus, persistent trauma to the mucosa overlying the pterygoid hamulus. The clinical features include strange chronic sensation, burning, swelling, and erythema of the pterygoid hamulus region. The pain often radiates to pharynx, ipsilateral face and sometimes radiating to temporal region making it difficult to diagnose from headache, temporomandibular disorders, and dental infections like pericoronitis. The anatomical neighboring structures in relation to oropharyngeal region may give a misleading diagnosis to dentist in case of pterygoid hamulus bursitis. The understanding of pterygoid hamulus anatomy and its relation to surrounding structures is necessary to get the correct diagnosis of the inflammatory or traumatic pain in oropharyngeal region.